Microclimate land surface temperatures across urban land use/ land cover forms - S. Ali; S. Patnaik; O. Madguni (Global Journal of Environmental Science and Management)
Urbanization brings biophysical changes in the composition of the landscape. Such change has an impact on the thermal environment locally. The urban mosaic of land use and land cover is thus characteristically composed of local climate zones. The spatial variation in the land surface temperature across specific zone is studied for Bhopal city. The objective of the study was to understand how the surface temperature varies with the spatial characteristics of the landscape. The green spaces had the lowest surface temperature that reaches to about 30.5 °C in parks with dense tree cover and highest mean normalized difference vegetation index value of about 0.5. The surface temperature was 36.1 °C for built up/barren areas. The study documents the correlation that exists between surface vegetation and surface temperature across the landscape of Bhopal city. The extent of tree cover and land surface temperature exhibited a strong negative correlation. A decrease in vegetation cover and successive increase in urban built up area were found to be related with high surface temperature. This implies that land surface temperature is an effective tool and may help city planners to make appropriate strategies for improving the tree resources of the urban landscape.